Occurrence, characterization, source, and risk assessment of petroleum-related hydrocarbons in sediments along St. Clair River, Ontario, Canada. (December 2021) - Yang, Zeyu; Shah, Keval; Laforest, Sonia; Courtemanche, Claire; Durand, William; Lambert, Patrick; Hollebone, Bruce P.; Brown, Carl E.; Goldthorp, Michael; Watson, Kevin; Yang, Chun; Dey, Diane; et al.
Abstract: Total petroleum hydrocarbons (TPH), n -alkanes, petroleum biomarkers, and polycyclic aromatic hydrocarbons (PAHs) were analyzed in the sediments collected from the shorelines and bottom of St. Clair River, Ontario, Canada. Most of the sampling sites had low TPH (< 20 μg/g). River bottom sediment usually had higher level of TPHs, total alkanes, total biomarkers, and total PAHs than most of the shoreline ones. Mixed biogenic and petrogenic n -alkanes were present in all the sites. Most sites had trace amounts of petroleum biomarkers. Mixed pyrogenic and petrogenic inputs with the predominant petroleum, have contributed to the detected PAHs at all sampling sites. PAHs detected would not show potential toxicity to benthic organisms in all shoreline sampling sites; however, some light molecular weight PAHs (e.g., phenanthrene, 2-methyl naphthalene, and acenaphthylene) are anticipated to have possible adverse impacts to sediment-dwelling organisms in part of the river bottom sediment. Highlights: All detected TPH did not exceed the criteria regulated by CCME. Higher level of petroleum hydrocarbons were detected in river bottom than shoreline of St. Clair. Mixed biogenic and petrogenic n -alkanes were present in all the sites. Mixed pyrogenic and petrogenic, especially petroleum contributed to PAHs at all sampling sites. Some 2-ring PAHs possibly have adverse impacts to sediment-dwelling organisms in river bottom.